Indecencia de la flexibilidad en la práctica de la cultura física en los niños y niñas del 7mo año básico de la escuela de educación básica Enrique Augusto Castro Aguilar, parroquia El Cambio, cantón Machala, periodo lectivo 2012-2013. - Chica Loayza, Cristhian Fernando (2014)
Today physical exercise daily in most people it is not very usual, work and other occupations not allow them take time to perform and in some cases, it's because you have no knowledge of how to execute them.